The main areas of dataspace realization - Shakhovska, Natalya; Medykovsky, Mykola; Byczkowska-Lipińska, Liliana (Видавництво Львівської політехніки, 2011)
Problems which arise up during work with separate information sources and databases are analyzed. Probletny, które pojawiają się podczas pracy z oddzielnych źródeł informaji i baz danych są analizowane.
Keywords: dataspace; datawarehouse; integration methods; consolidation; information product; dataspace; datawarehouse; integracji melody; konsolidacja; informacje o produkcie